2006
DOI: 10.1007/s00204-006-0117-x
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of tetrabromobisphenol A (TBBPA) in zebrafish (Danio rerio) in a partial life-cycle test

Abstract: Toxicological effects of the widely used flame retardant, tetrabromobisphenol A (TBBPA) were assessed in a partial life-cycle test with zebrafish (Danio rerio). Exposure of adult fish during 30 days to water-borne TBBPA in nominal concentrations ranging from 0 (control) to 1.5 M was followed by exposure of the offspring in early life stages up to 47 days posthatching (dph) to the same concentrations. Adults exposed to 3 and 6 M showed severe disorientation and lethargy shortly after beginning of exposure and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(53 citation statements)
references
References 31 publications
7
44
0
1
Order By: Relevance
“…This may have been caused by hepatic cellular swelling and fatty degeneration. This is consistent with observations of the effect of other BFRs on the liver [18,19]. We hypothesize that steatosis may be caused by: (1) an increase in fatty acid content in the hepatocytes; (2) over-synthesis of triglycercides; and (3) a decrease in apolipoprotein synthesis and inhibition of fat export.…”
Section: Discussionsupporting
confidence: 92%
“…This may have been caused by hepatic cellular swelling and fatty degeneration. This is consistent with observations of the effect of other BFRs on the liver [18,19]. We hypothesize that steatosis may be caused by: (1) an increase in fatty acid content in the hepatocytes; (2) over-synthesis of triglycercides; and (3) a decrease in apolipoprotein synthesis and inhibition of fat export.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, some previous studies showed that TBBPA could result in toxic effects on fish at high concentrations (Kuiper et al, 2007a;Hu et al, 2009). In the present study, no treatment-related deaths and abnormal behavior were observed in mosquitofish exposed to TBBPA.…”
Section: Expression Patterns Of Hormonal-response Genes In Mosquitofisupporting
confidence: 55%
“…Moreover, when tested with the Microtox and algal assays, TBBPA was significantly less toxic than tribromobisphenol (TrBBPA), dibromobisphenol (DBBPA), monobromobisphenol A (MBBPA) and bisphenol A (BPA) (Debenest et al, 2010). However, in some other studies, TBBPA was found to have a high toxicity to aquatic organisms (Kuiper et al, 2007a;Hu et al, 2009). Due to the structural resemblance to thyroid hormones (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have shown that TBBPA competes with T4 in its binding to the plasma-transporter protein, transthyretin (Hamers, 2006). TBBPA is acutely toxic in high concentrations and disrupts development and reproduction of zebrafish at low concentrations (Kuiper et al, 2006). Moreover, it impairs thyroid hormone-dependent metamorphosis in amphibian models (Fini et al, 2007;Jagnytsch et al, 2006).…”
Section: Introductionmentioning
confidence: 99%